Socio-economic factors affecting the acceptance of birth control methods among married women in Brgy. Mambatad, Miag-ao, Iloilo. - Manalo, Arnold Babad
This study seeks to determine if there is a relationship between some socio-economic factors like age, employment status, income, educational attainment and number of children the women already have and the acceptance or rejection of birth control methods among married women in Barangay Mambatad, Miagao. Specifically, it aims to answer the following objectives: 1.) To determine if there is a relationship between age and the acceptance of birth control methods among married women. 2.) To determine if there is a relationship between emplyment status and the acceptance of birth control methods among married women. 3) To determine if there is a relationship between income and the acceptance of birth control methods among married women. 4.) To determine if there is a relationship between educational attainment and the acceptance of birth control methods among married women. 5.) To determine if there is a relationship between the number of children the women already have and the acceptance of birth control methods among them. Married women are categorized in this study as acceptors and non-acceptors of birth control methods. The acceptors are those who accept, practice or use birth control methods whether natural or artificial while the non-acceptors are those who do not accept, practice or use birth control methods. Thirty (30) acceptors were selected out of the total 47 acceptors that the midwife listed while thirty (30) were also selected out of the total 51 non-acceptors. The interview schedule was used to gather data., The results of the study showed that there is no relationship between age and the acceptance of birth control methods: that there is no relationship between employment status and the acceptance of birth control methods; That there is no relationship between income and the acceptance of birth control methods; That there is no relationship between educational attainment and the acceptance of birth control methods; and finally, that there is no relationship between the number of children the women already have and the acceptance of birth control methods.